Effect of Amazonian dark earth fertility on nutritional status and fruit production of papaya (Carica papaya L.) in Central Amazonia - Falcão, Newton P.S. (Acta Amazonica, 2020)
The effect of Amazonian dark earth fertility on the nutritional status and fruit production of a Carica papaya plantation was evaluated in Açutuba Coast, Iranduba Municipality, Amazonas, Brazil, between August and Octuber 2003, when the plantation was eight months old and just starting production. A completely randomized experimental design, with four treatments and nine replications, was used; each replication contained three plants. The treatment were: Tpn - Amazonian Dark Earth with no supplemental fertilizer; Tpa - Amazonian Dark Earth with supplemental fertilizer (3 kg aged chicken manure and 300 g dolomite per plant); Tm1 - Mulata Earth with no supplemental fertilizer after cropping with squash; Tm2 - Mulata Earth with no supplemental fertilizer after slashing and burning fallow. The fruit production on Tpn (18.2 fruits/plant) was approximately 30% of the maximum production obtained on Tpa (61.1 fruits/plant); this effect was attributed to K which is low in Tpn and higher in Tpa because of the chicken manure. The potential acidity in all treatments was as expected in TP or TM, without apparent effect of previous soil management. There appeared to be a very large nutritional disequilibrium, caused by the high levels of P, Ca, Mg and low level of K. All treatments had levels Zn and Mn that are considered toxic, whereas Fe was suitable.